Copper nanoparticles biosynthesis by Priestia megaterium and its application as antibacterial and antitumor agents - Salma H. Mohamed; Badawi A. Othman; Basma T. Abd-Elhalim; Mohammed N. Abou Seada (Scientific Reports)
Abstract The growth of material science and technology places high importance on creating better processes for synthesizing copper nanoparticles. Thus, an easy, ecological, and benign process for producing copper nanoparticles (CuNPs) has been developed using Priestia sp. bacteria utilizing a variety of low-cost agro-industrial wastes and byproducts. The biosynthesis of CuNPs was conducted using glucose medium and copper ions salt solution, then it was replaced by utilizing low-cost agro-industrial wastes. UV–visible spectroscopy, dynamic light scattering (DLS), X-ray diffraction (XRD), High-resolution transmission electron microscope (HR-TEM), Attenuated Total Reflectance and Fourier transform infrared (ATR-FTIR), and zeta potential were used to characterize the biosynthesized CuNPs. The cytotoxicity of CuNPs using Vero -CCL-81 cell lines, and antibacterial and antitumor properties using human colon epithelial colorectal adenocarcinoma Caco-2-HTB-37 cell lines were assessed. The UV–visible and DLS studies revealed CuNPs formation, with a maximum concentration of 6.19 ppm after 48 h, as indicated by a 0.58 Surface plasmon resonance (SPR) within 450 nm and 57.73 nm particle size. The 16S rRNA gene analysis revealed that Priestia sp. isolate is closely related to Priestia megaterium and has been deposited in the NCBI GenBank with accession number AMD 2024. The biosynthesis with various agro-industrial wastes indicated blackstrap sugar cane molasses being the most effective for reducing CuNPs size to 3.12 nm owing to various reducing and stabilizing active compounds. The CuNPs were free of contaminants, with a sphere-shaped structure and a cytotoxicity assessment with an IC50 of 367.27 μg/mL. The antibacterial activity exhibited by the most susceptible bacteria were Bacillus cereus ATCC 11788 and Staphylococcus aureus ATCC 6538 with inhibition zones of 26.0 mm and 28.0 mm, respectively. The antitumor effect showed an IC50 dose of 175.36 μg/mL. Based on the findings, the current work sought to lower product costs and provide a practical solution to the environmental contamination issues brought on by the buildup of agricultural wastes. In addition, the obtained CuNPs could be applied in many fields such as pharmaceuticals, water purification, and agricultural applications as future aspects.